2016
DOI: 10.1039/c6ay02011a
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to predict protein aggregations using two-dimensional native protein microfluidic chip electrophoresis

Abstract: A microfluidic chip native protein electrophoresis was established to predict protein aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The advantages of microfluidic electrophoresis include low-sample requirements, cost-efficiency, rapid detection, as well as convenient integration with sensing modules [123]. Some examples of types of electrophoretic methods that have been implemented in microfluidic devices include gel electrophoresis, capillary electrophoresis, and dielectrophoresis [124,125]. Figure 15.…”
Section: How To Detect On-sitementioning
confidence: 99%
“…The advantages of microfluidic electrophoresis include low-sample requirements, cost-efficiency, rapid detection, as well as convenient integration with sensing modules [123]. Some examples of types of electrophoretic methods that have been implemented in microfluidic devices include gel electrophoresis, capillary electrophoresis, and dielectrophoresis [124,125]. Figure 15.…”
Section: How To Detect On-sitementioning
confidence: 99%
“…Neurological diseases including multiple sclerosis [104], epilepsy [105,106], bipolar disorder [107,108], and Alzheimer's disease [109][110][111][112] were investigated…”
Section: Neurological Diseasesmentioning
confidence: 99%
“…The time for sample-in-answer-out was 3.5 min including analyte separation in 30 s.2.3.4 Alzheimer's diseaseAlzheimer's disease is a neurodegenerative disease that is associated with elevated levels of phosphorylated tau protein and β-amyloids, and the toxic protein aggregation in the brain. An on-chip hyphenation of isoelectric focusing and zone electrophoresis strategy was applied to study protein aggregation[109]. The β-amyloid peptides were investigated by immunocapture of the peptides from cerebrospinal fluids and subsequent electrophoretic enrichment and separation prior to the fluorescence[110] and mass spectrometric detection[111].…”
mentioning
confidence: 99%
“…The analysis employed a two-dimensional separation approach involving a combination of isoelectric focusing and capillary zone electrophoresis. 93 The combined platform allowed the time-course of α-synuclein aggregation to be studied and provided a strategy for real-time detection of early and intermediate species on the aggregation pathway. As part of the study it was shown that the chip could be used to analyse the effect of small molecules on the aggregate formation process and could as such serve as a platform for screening for potential aggregation inhibitors.…”
Section: Interactions Between Amyloid Structures and Other Moleculesmentioning
confidence: 99%